Slower progression of central puberty in overweight girls presenting with precocious breast development - Mi Ra Kim; Mo Kyung Jung; Eun-Gyong Yoo (Korean Society of Pediatric Endocrinology, 2022)
Purpose Overweight (OW)/obese girls tend to have an earlier pubertal onset than girls with normal weight. However, only a few studies have reported the progression of puberty in these girls. This study aimed to identify risk factors for rapid pubertal progression in OW/obese girls presenting with precocious breast development. Methods This retrospective cohort study reviewed the medical records of 110 OW (body mass index [BMI] ≥85th percentile for age and sex) and 213 nonoverweight (NW, BMI <85th percentile for age and sex) girls who presented with breast budding before 8 years of age. OW girls were divided into 2 subgroups: girls with central puberty progression before 9 years of age (OW-RP) and those without (OW-SP). Results Progression to central puberty before the age of 9 was more common in NW girls than in OW girls (83.8 % vs. 65.2 % in NW vs. OW group, p<0.001), and progression-free survival for 1, 2, and 3 years was higher in the OW group (p<0.001). In a subgroup analysis of OW girls, the OW-RP subgroup had more advanced bone age (BA) at the first visit (p=0.047) and higher initial luteinizing hormone (LH, p=0.010) levels than the OW-SP subgroup. Being NW (p=0.001) and having more advanced BA (p=0.023) at the initial workup were the risk factors for pubertal progression before age 9. Conclusions Pubertal progression seems to be slower in OW girls than in NW girls presenting with precocious breast development. However, it can progress rapidly in OW girls with particularly pronounced BA advancement and high LH levels at the initial workup.